Enhancing professionalism of first-year medical students through early nursing practice training and attitude education - Ryoko Igarashi (Korean Journal of Medical Education, 2023)
Purpose This study aimed to clarify the attitudes, behaviors, and learning experiences of first-year medical students participating in a nursing practice training aimed at enhancing their professionalism. Methods A questionnaire survey was conducted among first-year medical students after their nursing practical training to understand their learning experiences. Descriptive statistics was performed for each questionnaire item. For free-text responses, descriptions were grouped by input data with similar content and meaning, and analyzed qualitatively. Others’ evaluation and self-evaluation were analyzed quantitatively. Results Most students were actively engaged and fulfilled in the training. The free comments generated these categories: “nursing care,” “roles of nurses,” “patient impressions,” “multidisciplinary cooperation,” “communication,” and “what is required of physicians. On the first day, all items evaluated had higher mean scores in the others’ evaluation than in the self-evaluation. On the second day, for “maintains standards of personal appearance (including uniform, hair, and name tag),” the others’ evaluation means were higher than the self-evaluation means. T-tests showed a significant difference in “maintains standards of personal appearance (including uniform, hair, and name tag)” (t=-2.103, degrees of freedom [df]=71.104, p<0.05) and “attends to patients with a polite manner” (t=-2.087, df=74, p<0.05) for both the high and low groups. Conclusion Greeting, appearance, communication skills, and attitude were found to be the important bases of attitude education in the nursing training ideally involving multidisciplinary professionals. The medical students were able to grasp what is required of doctors and objectively view such position from the viewpoints of nurses and patients.